2009 3rd International Conference on Signals, Circuits and Systems (SCS) 2009
DOI: 10.1109/icscs.2009.5414173
|View full text |Cite
|
Sign up to set email alerts
|

SAW-properties of langasite at high temperatures: Measurement and analysis

Abstract: The measurement range of temperature using SAW-devices is depending on the substrate material used in the measurements. This dependence is related to the temperature point, where the substrate loses its piezoelectric properties. This occurs by the SAW-materials such as quartz and lithium niobate at about 570°C or 350°C, respectively. The piezoelectric material langasite (La3Ga5SiO14) has a thermodynamically stable phase and do not lose its piezoelectric properties up to its melting point at about 1470 °C and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…We can find the SAW velocity of YCOB is higher than that of LGS. These results are very close to the reported data [10,11]. 5 shows relative frequency shift in resonance frequency as a function of temperature from room temperature up to 600 °C, where f r0 is the resonance frequency at room temperature.…”
Section: Resultssupporting
confidence: 80%
“…We can find the SAW velocity of YCOB is higher than that of LGS. These results are very close to the reported data [10,11]. 5 shows relative frequency shift in resonance frequency as a function of temperature from room temperature up to 600 °C, where f r0 is the resonance frequency at room temperature.…”
Section: Resultssupporting
confidence: 80%
“…Measurements on single crystal bulk resonators were made by Johnson et al [30] who observed increasing acoustic loss up to 700 K. Schreuer et al [31] also saw increasing loss with temperature in single-crystal langasite and examined the effect of frequency and annealing ambient. An increase in surface wave attenuation in SAW devices with temperature and frequency was subsequently observed [3234]. Shrena et al reported lower losses for the (0°, 138°, 27°) orientation than the (0°, 30°, 27°) and also higher losses when metal was on the propagation path [33,34].…”
Section: Langasite As a Saw Substratementioning
confidence: 99%
“…An increase in surface wave attenuation in SAW devices with temperature and frequency was subsequently observed [3234]. Shrena et al reported lower losses for the (0°, 138°, 27°) orientation than the (0°, 30°, 27°) and also higher losses when metal was on the propagation path [33,34]. These acoustic losses represent a significant obstacle to the development of high-temperature sensors as they reduce signal strength at high temperature and limit the maximum frequency of operation.…”
Section: Langasite As a Saw Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Among various piezoelectric materials, langasite (LGS) has been thought as one of the most attractive material in high temperature due to its good temperature stability and large coupling constant K 2 (0.34%), which is two times larger than that of ST-quartz (0.14%) [5]. Haifeng Zhang [6] reported the force-frequency effect of LGS resonators.…”
Section: Introductionmentioning
confidence: 99%